The "lady in white", a showy new species of Cryptocentrum (Orchidaceae, Maxillariinae) from Colombia - C., German Carnevali F.; V., Pedro Ortiz; Peraza-Flores, Lizandro N. (Phytotaxa, 2012)
Cryptocentrum misasii P.Ortiz & Carnevali is described and illustrated. This distinctive, showy new species has been collected only once in western Colombia at Cerro Mecana, Serranía del Baudó (Chocó), at 800–1000 m elevation. Cryptocentrum misasii is easily distinguished from all other species of Cryptocentrum by its large white flowers. On morphological grounds, it is referable to subgenus Cryptocentrum due to its monopodial habit, distichous leaves, and ovary plus spur totally enclosed by the floral bract. Within subgenus Cryptocentrum, C. misasii is most similar to C. dodsonii, from which it is amply distinct by its large flowers with sepals of up to 24.5 mm (vs. 9.5–16.0 mm in C. dodsonii) and white perianth segments (vs. bright yellow to yellow or yellow-green in C. dodsonii). Identifications are provided for the Cryptocentrum species featured in Dr. Misas-Urreta's book on the orchids of the Serranía del Baudó. The conservation status of the species was assessed as Critically Endangered (D) by the IUCN criteria.